Magnitude of second-trimester-induced abortion and associated factors among women who received abortion service at public hospitals of Arba Minch and Wolayita Sodo towns, southern Ethiopia: A cross-sectional study - Mesfin Abebe; Abera Mersha; Nega Degefa; Wondwosen Molla; Aregahegn Wudneh (Frontiers Media S.A., 2022)
IntroductionSecond-trimester abortion accounts for 10-15% of all induced abortions, with varying rates across countries, and is responsible for two-thirds of major abortion complications. It is also associated with higher medical costs, morbidity, and mortality rates than first-trimester abortion. Even though it is a significant burden, there is a lack of adequate information about second-trimester-induced abortion, especially in the study area. As a result, the primary purpose of this study is to fill this research gap and assess the magnitude and associated factors of second-trimester-induced abortion in the public hospitals of Arba Minch and Wolayita Sodo towns, southern Ethiopia.MethodsA facility-based cross-sectional study was conducted. Systematic sampling was used to select 353 study participants. Data were collected through face-to-face interviews using a structured questionnaire and record review by using Kobo collect version 3.1. Analysis was done by STATA 14. Logistic regression was used to identify associated factors of the second-trimester-induced abortion.ResultsThe magnitude of second-trimester-induced abortion in the study setting was 23% (95%CI: 18.5%, 27.4%). The factors associated with second-trimester-induced abortion among women received abortion care services were respondent's age 25-29 and 30-34 years old (AOR = 0.38, 95%CI:0.15, 0.96 and (AOR = 0.31, 95%CI:0.10, 0.97, respectively), planned pregnancy (AOR = 0.22, 95%CI:0.11, 0.44), and delay confirming pregnancy (AOR = 2.21, 95%CI:1.15, 4.23).ConclusionThis study showed that more than one-fifth of women who presented for abortion care services had second-trimester-induced abortions. Health institution organizations working on maternal health at various levels should provide counseling to women to help them early confirm their pregnancy and make decisions about whether or not to continue it as early as possible.